Mental Health Screening, Treatment, and Institutional Incidents: A Propensity Score Matched Analysis of Long-Term Outcomes of Screening. Issue 2 (3rd April 2018) - Martin, Michael S.; Wells, George A.; Crocker, Anne G.; Potter, Beth K.; Colman, Ian
ABSTRACT: There is little study of the impacts of screening on distal outcomes such as recovery or adverse incidents during incarceration. Furthermore, screening practices vary greatly between jurisdictions; many focus on history taking as opposed to current symptoms. Method . We conducted an observational cohort study of all admissions ( N = 13, 281) to Canadian prisons over a 33-month period. We used full matching on propensity scores to explore the association between treatment and health, violent and victimization incidents. Results . Treatment was associated with lower rates of victimization and violence for all inmates, and health incidents among screen-detected cases. Among inmates with pre-existing risk–who accounted for 90% of health incidents—treatment was associated with increased risk of a first incident but decreased risk of recurrent incidents. Implications . In-depth symptom-based screening identified a group of inmates who benefited from treatment, but accounted for relatively few incidents. Tensions of prioritizing resources for pre-existing vs, incident mental illness were highlighted by weaker treatment effects for those with pre-existing needs. Increased use of diversion options to keep inmates with mental illness out of prisons, and determining the appropriate intensity of intervention to meet the needs of screen-detected cases could alleviate some of these tensions.